Management of cardiovascular surgery in patients with systemic lupus erythematosus including thromboembolism and multiple organ failure prevention: A retrospective observational study. Issue 7 (17th February 2023) - Yamamoto, Taira; Matsushita, Satoshi; Endo, Daisuke; Shimada, Akie; Dohi, Shizuyuki; Kajimoto, Kan; Yokoyama, Yasutaka; Sato, Yuichiro; Machida, Yoichiro; Asai, Tohru; Amano, Atsushi
Abstract : Systemic lupus erythematosus is a chronic autoimmune disease that affects most tissues. Cardiovascular events are critical, life-threatening, long-term complications of systemic lupus erythematosus (SLE). We report our single-center experience of performing cardiovascular surgery in patients with SLE while avoiding postoperative complications. We also suggest a new approach for cardiopulmonary bypass and perioperative management. We applied the antiphospholipid antibody syndrome (APS) severity classification published by the Japan Intractable Disease Information Center to patients with SLE for perioperative management. Patients with Grade III or higher severity are treated with a slightly relaxed version of catastrophic APS therapy. This treatment modality includes glucocorticoids, anticoagulation, intravenous immunoglobulin, and plasma exchange. Between April 2010 and January 2021, 26 patients (2 males, 24 females) with SLE underwent cardiovascular surgery. The mean age was 74.2 ± 13.0 years (38–84 years). The primary outcomes were in-hospital mortality and long-term results, and the secondary outcomes were related to bleeding/embolization and coagulation function/platelet count. A subset analysis was performed to examine treatment efficacy in the APS Grade III or higher group. Of the 26 patients, 17 underwent valve surgery, 4 underwent isolated coronary artery bypass grafting, and 5 underwent thoracic aortic aneurysm surgery. There were no in-hospital deaths or associated bleeding/embolic complications. Postoperative antithrombin III decreased in patients who underwent valvular and aortic surgery, and platelet counts recovered to preoperative levels within 7 to 10 days. The 5- and 10-year survival rates were 80.5% and 53.7%, respectively. In addition, there were 10 patients with APS Grade III or higher, but there was no significant difference in the frequency of complications other than platelet recovery after treatment. The surgical outcome of open-heart surgery in patients with SLE was good. Surgical treatment of cardiovascular disease in these patients is difficult and complex. We focused on blood coagulation abnormalities and treated each patient by selecting the best individual treatment protocol according to the severity of the disease, taking into account the risk of bleeding and thrombosis. Management of blood coagulation function in these patients is essential, and careful therapeutic management should be considered during open-heart surgery.